2012
DOI: 10.1128/jvi.01220-12
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Early Temporal and Spatial Interaction of the Sindbis Virus Capsid and E2 Proteins with Reverse Genetics

Abstract: A 7-Å cryoelectron microscopy-based reconstruction of Sindbis virus (SINV) was recently generated. Fitting the crystal structure of the SINV capsid protein (Cp) into the density map revealed that the F2-G2 loop of the Cp was shifted away from cytoplasmic domain of E2 (cdE2) in the 7-Å reconstruction relative to its position in the Cp crystal structure. Furthermore, the reconstruction demonstrated that residue E395 in region I of the cytoplasmic domain of the E2 envelope protein (cdE2-RI) and K252 of Cp, part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…The commonly accepted hypothesis regarding alphavirus particle assembly is that NCs are formed in the cytoplasm of infected cells, and this process is mediated by interaction of the capsid protein with the RNA packaging signal (PS), which is present in genomic, but not subgenomic, RNA. The NCs are then transported to the plasma membrane either by themselves or on the surfaces of membranous vesicles, the so-called CPVII, and then bud from the cells while acquiring their lipid envelope with glycoprotein spikes (27,28). NC itself has an icosahedral geometry and apparently determines the final alphavirus T4 symmetry.…”
mentioning
confidence: 99%
“…The commonly accepted hypothesis regarding alphavirus particle assembly is that NCs are formed in the cytoplasm of infected cells, and this process is mediated by interaction of the capsid protein with the RNA packaging signal (PS), which is present in genomic, but not subgenomic, RNA. The NCs are then transported to the plasma membrane either by themselves or on the surfaces of membranous vesicles, the so-called CPVII, and then bud from the cells while acquiring their lipid envelope with glycoprotein spikes (27,28). NC itself has an icosahedral geometry and apparently determines the final alphavirus T4 symmetry.…”
mentioning
confidence: 99%
“…The studies performed on different alphaviruses also indicated the existence of two mechanisms in virion assembly. The first mechanism suggests preformation of the nucleocapsids in the cytoplasm, followed by their migration to the plasma membrane either by passive diffusion or at the surface of previously described cytopathic vacuoles (CPVII) (28)(29)(30)(31). Such preformed NCs and CPVII vesicles are readily detectable by EM in the cytoplasm of virus-infected cells.…”
Section: Discussionmentioning
confidence: 91%
“…isolated from infected cells versus those isolated from virus particles (28). Consideration of these and other data suggested that the interaction of the envelope proteins with the capsid proteins could promote nucleocapsid maturation during budding of virus particles (5,11,29,30). The importance of envelope interactions in nucleocapsid maturation is in keeping with a temperature-sensitive capsid mutant, in which unstable cytoplasmic nucleocapsids are stabilized upon budding into virus particles (19).…”
Section: Figmentioning
confidence: 83%
“…Both the capsid protein and the envelope proteins form organized lattices, but the relative importance of the nucleocapsid lattice versus the envelope protein lattice in promoting particle assembly and budding is unclear (reviewed in reference 4). Nucleocapsids assemble in the cytoplasm of infected cells in the absence of envelope protein expression (10,11), and purified capsid protein can also assemble into nucleocapsid-like structures when incubated with RNA in vitro (12)(13)(14)(15). However, interaction of intracellular nucleocapsids with the envelope proteins is clearly required for virus particle production, as discussed above.…”
mentioning
confidence: 99%
See 1 more Smart Citation